KEPEMIMPINAN TRANSFORMATIF KEPALA MADRASAH ALIYAH AL-AMIRIYYAH BLOKAGUNG - Zainal Abidin; Lutfi Wakhid; Ravilla Naflah Salsabila (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2022)
The head of the madrasa is the leader of the education unit. The success of the principal's leadership is based on one theory or model of leadership. Transformative leadership is leadership that is able to change the energy of resources, both people, instruments, and situations to achieve goals. This study used qualitative research methods. This research was conducted at MA Al-Amiriyyah Blokagung Tegalsari Banyuwangi. The research data use primary data derived from interviews and observations and secondary data derived from documents. This type of research uses case studies. The purpose of this study was to determine the transformative leadership of the madrasah principal at MA Al-Amiriyyah Blokagung Tegalsari Banyuwangi. The results of this study indicate: 1) The principal as an agent of renewal or change is able to increase the number of students who register, 2) The principal as a role model is able to be disciplined and optimistic in every matter, 3) The principal as a driver of subordinate performance is able to increase the morale of subordinates by giving rewards or praise to their subordinates who are active and also able to build enthusiasm for passive teachers by providing motivation, 4) The principal is able to overcome problems by being a mediator and decision maker through deliberation and accepting ideas from any party, and asking for solutions directly from their subordinates, 5) The madrasah principal is able to improve his abilities by continuously honing his abilities through special training, not only that, he also increases the quality of his subordinates so that the quality of learning in the madrasa is guaranteed, 6) the madrasah principal is able to act according to the value system with respect full responsibility for every affairs of the institution.